1988
DOI: 10.1111/j.1365-2044.1988.tb05658.x
|View full text |Cite
|
Sign up to set email alerts
|

Rectus sheath block for diagnostic laparoscopy

Abstract: Summary Sixtj, adult jeniules of'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 1 publication
1
65
0
1
Order By: Relevance
“…6,7 Although simple to perform, there remain concerns regarding the accuracy of needle placement. The results of this study in adult patients show that local anesthetic placement in the rectus sheath block by LOR is accurate in only 45% of abdominal punctures, and the success rate decreased significantly as BMI increased.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although simple to perform, there remain concerns regarding the accuracy of needle placement. The results of this study in adult patients show that local anesthetic placement in the rectus sheath block by LOR is accurate in only 45% of abdominal punctures, and the success rate decreased significantly as BMI increased.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that by using this technique, the requirements for postoperative analgesia were reduced significantly in abdominoplasty patients. In adults, the rectus sheath block has been shown to improve patient comfort after laparoscopic surgery, suggesting that it might be an alternative to epidural anesthesia for some surgical procedures [2]. Although regional anesthetic techniques are commonly used for postoperative pain control in pediatric anesthesia, there were very few data about rectus sheath block.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the block has been renewed following reports of its analgesic efficacy in adults undergoing laparoscopy and in children for para-umbilical and umbilical hernia repair [2][3][4]. Studies in adults and children have compared the rectus sheath block with opioids alone for analgesia after laparoscopic surgery, showing favorable results [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Smith BE [5] et al, studied BRSB in diagnostic laparoscopy and compared with control group. They used 15ml of Bupivacaine 0.25% at the end of the operation.…”
Section: Discussionmentioning
confidence: 99%